1976
DOI: 10.1042/bj1570033
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of ornithine decarboxylase in liver of control and growth-hormone-treated rats

Abstract: 1. Ornithine-2-oxo acid aminotransferase activity was inhibited by amino-oxyacetate (10(-5) M). This permitted the measurement of ornithine decarboxylase in the presence of mitochondria by using the 14CO2-trapping technique. 2. Subcellular fractionation of rat liver by differential centrifugation, followed by the assay of ornithine decarboxylase in the presence of amino oxyacetate and of marker enzymes for each fraction, demonstrated that ornithine decarboxylase was located in the cytosol. 3. The greatly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Previous studies on the effect of GH on liver enzymes in intact animals have demonstrated increases in the activities of ornithine decarboxylase (22,23), alanine aminotransferase (24), and DNA polymerase (25) after the injection of a single dose of GH. In this study, the administration of a single dose of GH had no effect on liver alcohol dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effect of GH on liver enzymes in intact animals have demonstrated increases in the activities of ornithine decarboxylase (22,23), alanine aminotransferase (24), and DNA polymerase (25) after the injection of a single dose of GH. In this study, the administration of a single dose of GH had no effect on liver alcohol dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…AOAA is an inhibitor of transaminases and at the concentration used, ornithine-2-oxo acid aminotransferase (EC 2.6.1.13) is virtually completely inhibited (14). The latter enzyme is on a pathway whereby the carboxyl group of ornithine is transformed by transamination to glutamic semialdehyde and thence to glutamate (15) mination and entry of 2-oxoglutarate into the tricarboxylic acid cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In some eucaryotic cells, such as normal rat liver (Murphy and Brosman, 1976;Bartholens, 1983), chick embryos (Snyder and Kreuz, 1970), and T. pyriformis (Sklaviadis et al, 1985) ODC has been found in the nucleus. In germinated barley, corn, pea and bean seeds ODC is located both in the cytosol and in the nucleus tightly bound to chromatin (Panagiotidis et al, 1982;Foudouli and Kyriakidis, 1989).…”
Section: Introductionmentioning
confidence: 98%